2010
DOI: 10.1016/j.jcrs.2010.05.027
|View full text |Cite
|
Sign up to set email alerts
|

Laser in situ keratomileusis flap complications using mechanical microkeratome versus femtosecond laser: Retrospective comparison

Abstract: Although the total complication rates between the 2 groups were similar, the microkeratome group had significantly more epithelial defects intraoperatively and the femtosecond laser group had significantly more DLK cases postoperatively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
101
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(111 citation statements)
references
References 28 publications
2
101
1
Order By: Relevance
“…In femto-LASIK surgery, for example, personalized determination of optical properties could lead to more favorable outcomes by reducing complications stemming from patient-to-patient variability and improper pulse energy selection, such as transient light sensitivity, diffuse lamellar keratitis, and buttonhole formation. 1 The ideal method would determine the scattering properties and ablation thresholds in thick, unsectioned, multilayered, and inhomogeneous tissue without complex simulations. Current methods do not meet these requirements.…”
mentioning
confidence: 99%
“…In femto-LASIK surgery, for example, personalized determination of optical properties could lead to more favorable outcomes by reducing complications stemming from patient-to-patient variability and improper pulse energy selection, such as transient light sensitivity, diffuse lamellar keratitis, and buttonhole formation. 1 The ideal method would determine the scattering properties and ablation thresholds in thick, unsectioned, multilayered, and inhomogeneous tissue without complex simulations. Current methods do not meet these requirements.…”
mentioning
confidence: 99%
“…10,11 Femtosecond lasers are now used by more than 50% of LASIK surgeons in the United States. A It has been shown that experience accumulated by surgeons as a group significantly improves outcomes compared with an individual surgeon.…”
mentioning
confidence: 99%
“…11,12 While rare, partial flaps are one of the most common complications related to mechanical microkeratome flap creation in LASIK. [13][14][15] For this reason it is important to have a good strategy for managing partial flaps that minimizes the increased incidence of complications related to recutting a second flap. 3,4,16 A direct measurement of the thickness profile of the partial flap is essential to assess the risks of creating a second flap, and using a femtosecond laser brings the advantages of good reproducibility and flap thickness uniformity as well as the ability to program the flap thickness to the nearest micron.…”
Section: Discussionmentioning
confidence: 99%